ANALYSIS OF ELASTICITY IN WOODS SUBMITTED TO THE STATIC BENDING TEST USING THE PARTICLE IMAGE VELOCIMETRY (PIV) TECHNIQUE - Pereira,Rodrigo A. (2018)
ABSTRACT The most important parameter in terms of material mechanical behavior knowledge is the modulus of elasticity, being traditionally obtained through destructive tests. The objective of this study is the verification of the potential use of the particle image velocimetry technique (PIV) as a tool to obtain the modulus of elasticity in sawed wood samples (Pinus oocarpa and Eucaliptus grandis) and wood panels (Plywood, LVL and OSB). The PIV technique has as characteristics the low cost of equipment, fast results, no need for contact with the object tested, accuracy and possibility of application in the field. The application of the PIV technique occurred during the static bending tests where the deformations were also measured with a dial indicator (conventional method), thus obtaining comparative measurements. From the load values applied by a universal test machine and deformation values obtained by the dial indicator and PIV techniques, it was possible to calculate the modulus of elasticity through both methods. With the “Student's t” statistical test application with significance level of 1%, it was verified that the modulus of elasticity found by the PIV technique and the dial indicator were statistically equal. Average values for the modulus of elasticity found were respectively for the use of the conventional method and for the PIV method the values of: 13,077 and 13,027 MPA for Eucalyptus grandis; 6,171.6 and 6,418.8 MPa for Pinus oocarpa; 10,481.2 and 11,094.3 MPa for plywood; 8,687.4 and 10,261.0 MPa for the LVL; and 2,480.1 and 2,899 MPa for the OSB. It was concluded that the PIV technique is capable of measuring modulus of elasticity values with similar precision to the test techniques traditionally used for this purpose.